Research on radial crack propagation of railway brake disc under emergency braking conditions. (January 2023) - Lu, Chun; Shen, Jiacheng; Fu, Qiang; Mo, Jiliang
Highlights: The failure of railway brake discs caused by crack propagation is studied. The competitive relationship between the crack growth along the radial and thickness directions is discussed. The evolution of crack propagation behaviors of the railway brake disc is investigated. The proposal for braking safety improvement is presented. Abstract: The fatigue damage of the brake disc significantly impacts the braking safety of railway trains. This paper takes the emergency braking condition of 270 km/h as an example to analyze the fatigue crack propagation problem of the brake disc. With the help of theoretical analysis and thermomechanical finite element simulation, the crack propagation behaviors of the brake disc following radial and thickness directions are studied based on comprehensively considering crack threshold, fracture toughness, and the specified brake disc crack limit length. The research results show that the crack growth rate of the brake disc following the radial direction is greater than that in the thickness direction. However, since the thickness dimension is much smaller than the radial dimension, the crack propagation along the thickness direction may lead to crack penetration through the thickness, and unstable propagation will happen when the crack length reaches 60 mm. In addition, it is found that when the crack length is half the specified limit length, the crack propagation life accounts for more than 90% of the brake disc's entire crack propagation life. Under the calculation conditions of this work, the permissible limit length of the radial cracks can be reduced from 80 mm to 40 mm, which has little impact on the brake disc's service life while ensuring braking safety.